Characteristics of Decreased Pulmonary Function and Clinical Symptoms in Nickel Electroplating Workers. Issue 4 (April 2018) - Tsao, Yu-Chung; Chang, Ya-Ching; Gu, Po-Wen; Tzeng, I-Shiang; Luo, Jiin-Chyuan John
Abstract : Objective: To investigate health problems, especially pulmonary function, among electroplating workers exposed to nickel. Methods: We recruited 153 nickel-exposed and 74 control workers from electroplating shops in printed circuit board production plants. Questionnaires were conducted to collect basic information. Symptoms and pulmonary function were ascertained. Results: The average urine nickel level of the 79 high-exposure, 74 low-exposure, and 74 control workers were 7.38 ± 5.96, 5.79 ± 4.75, and 5.27 ± 3.89 μg/g Cr, respectively. Nickel-exposed workers had a significantly higher incidence of skin- and airway-based symptoms. A significant relationship between impaired pulmonary function and high (more than5.2 μg/g Cr) urine nickel level was observed. Conclusions: Nickel-exposed workers had significantly higher urine nickel levels with more skin-, airway-based symptoms, as well as impaired pulmonary function. A dose–response relationship between decreased pulmonary function and nickel exposure status was observed.